1996
DOI: 10.1074/jbc.271.42.25864
|View full text |Cite
|
Sign up to set email alerts
|

Secobarbital-mediated Inactivation of Cytochrome P450 2B1 and Its Active Site Mutants

Abstract: Secobarbital (SB) is a relatively selective mechanismbased inactivator of cytochrome P450 2B1, that partitions between epoxidation and heme and protein modification during its enzyme inactivation. The SB-2B1 heme adduct formed in situ in a functionally reconstituted system has been spectrally documented and structurally characterized as N-(5-(2-hydroxypropyl)-5-(1-methylbutyl)barbituric acid)protoporphyrin IX. The SBprotein modification has been localized to 2B1 peptide 277-323 corresponding to the active site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…A variety of compounds containing an olefinic bond, such as ethylene, allylisopropylacetamide (AIA), and secobarbital, can form covalent adducts on the nitrogen of the porphyrin group of the prosthetic heme leading to inactivation [382][383][384][385] Secobarbital has been shown to completely inactivate CYP2B1 with only partial loss of the heme chromophore [384,386,387] Isolation of the modified CYP2B1 protein and the N-alkylated porphyrins indicates that the reactive compound partitions between protein modification, N-alkylation of the heme, and formation of an epoxide metabolite in the ratio of 02:08:59, respectively [387] (Fig 517) The formation of a heme adduct in the active site of CYP2B1 was confirmed spectrally based on its typical absorption maximum at ~ 445 nm, a characteristic fea- ture of iron complexed N-modified porphyrins [388] The modified CYP2B1 peptide has been isolated and shown to span residues 277-323 By sequence analogy, these residues correspond to the distal I helix in P450 cam [386,[389][390][391][392] Further digestion of the modified peptide has resulted in identification of the site for modification by secobarbital to a residue in the peptide G299-S304 [387] Although the identity of the adducted residue has not yet been determined, these results are consistent with modification of the CYP2B1 in the active site Specific mutations of CYP2B1 in the putative substrate-recognition site (SRS) 2,4,5, and 6, but not in SRS-1, cause a decrease in the inactivation by secobarbital Mutation of residue 367 from V to A in SRS-5 had a marked inhibitory effect on protein modification [387] Isolation of the N-modified porphyrins as the parent adducts as well as the corresponding dimethylesters and analysis by LC-MS demonstrated the formation of adducts of hydroxysecobarbital with protoporphyrin IX (Fig 517) [386] Like terminal olefins, terminal acetylenes can alkylate the P450 prosthetic heme However, compounds such as 10-undecynoic acid, 1-ethynylpyrene, 2-ethynylnaphthalene, 9-ethynylnaphthalene, 17β-ethynylprogesterone, and 17α-ethynylestradiol (EE) inactivate P450s primarily by covalently binding to the apoprotein with little or no effect on the heme group (Fig 518) [305, 310, 317, 318] Almost stoichiometric binding of 10-undecynoic acid to rat liver CYP4A1 (the ω-hydroxylase) as well as of 2-ethynylnaphthalene and 1-ethynylpyrene to CYP1A1 and -1A2, and of EE to CYP3A4 has been observed [305]…”
Section: Olefins and Acetylenesmentioning
confidence: 99%
“…A variety of compounds containing an olefinic bond, such as ethylene, allylisopropylacetamide (AIA), and secobarbital, can form covalent adducts on the nitrogen of the porphyrin group of the prosthetic heme leading to inactivation [382][383][384][385] Secobarbital has been shown to completely inactivate CYP2B1 with only partial loss of the heme chromophore [384,386,387] Isolation of the modified CYP2B1 protein and the N-alkylated porphyrins indicates that the reactive compound partitions between protein modification, N-alkylation of the heme, and formation of an epoxide metabolite in the ratio of 02:08:59, respectively [387] (Fig 517) The formation of a heme adduct in the active site of CYP2B1 was confirmed spectrally based on its typical absorption maximum at ~ 445 nm, a characteristic fea- ture of iron complexed N-modified porphyrins [388] The modified CYP2B1 peptide has been isolated and shown to span residues 277-323 By sequence analogy, these residues correspond to the distal I helix in P450 cam [386,[389][390][391][392] Further digestion of the modified peptide has resulted in identification of the site for modification by secobarbital to a residue in the peptide G299-S304 [387] Although the identity of the adducted residue has not yet been determined, these results are consistent with modification of the CYP2B1 in the active site Specific mutations of CYP2B1 in the putative substrate-recognition site (SRS) 2,4,5, and 6, but not in SRS-1, cause a decrease in the inactivation by secobarbital Mutation of residue 367 from V to A in SRS-5 had a marked inhibitory effect on protein modification [387] Isolation of the N-modified porphyrins as the parent adducts as well as the corresponding dimethylesters and analysis by LC-MS demonstrated the formation of adducts of hydroxysecobarbital with protoporphyrin IX (Fig 517) [386] Like terminal olefins, terminal acetylenes can alkylate the P450 prosthetic heme However, compounds such as 10-undecynoic acid, 1-ethynylpyrene, 2-ethynylnaphthalene, 9-ethynylnaphthalene, 17β-ethynylprogesterone, and 17α-ethynylestradiol (EE) inactivate P450s primarily by covalently binding to the apoprotein with little or no effect on the heme group (Fig 518) [305, 310, 317, 318] Almost stoichiometric binding of 10-undecynoic acid to rat liver CYP4A1 (the ω-hydroxylase) as well as of 2-ethynylnaphthalene and 1-ethynylpyrene to CYP1A1 and -1A2, and of EE to CYP3A4 has been observed [305]…”
Section: Olefins and Acetylenesmentioning
confidence: 99%
“…Some examples include: 1) studies have demonstrated that Thr302 in CYP2B1 and Thr302 in CYP2B4 are critical determinants for secobarbital and 2EN inactivation, respectively (He et al, 1996;Roberts et al, 1996) and 2) a decrease in the inactivation of 2E1 by 5-phenyl-1-pentyne and several naturally occurring isothiocynates and the reversible formation of a novel heme adduct of tert-butylacetylene were observed in the Thr303A mutant of 2E1 (Roberts et al, 1998;Moreno et al, 2001;Blobaum et al, 2004).…”
Section: ϫ5mentioning
confidence: 99%
“…Conversely, the 0.20 lM Ca 2? , causing less ionization of the indole moiety, resulted in heme adducts formation as suggested by the 448 nm peak [64,65].…”
Section: Discussionmentioning
confidence: 99%